Multitarget fatty acid amide hydrolase/cyclooxygenase blockade suppresses intestinal inflammation and protects against nonsteroidal anti‐inflammatory drug‐dependent gastrointestinal damage. Issue 6 (10th March 2015) - Sasso, Oscar; Migliore, Marco; Habrant, Damien; Armirotti, Andrea; Albani, Clara; Summa, Maria; Moreno‐Sanz, Guillermo; Scarpelli, Rita; Piomelli, Daniele
ABSTRACT: The ability of nonsteroidal anti‐inflammatory drugs (NSAIDs) to inhibit cyclooxygenase (Cox)‐1 and Cox‐2 underlies the therapeutic efficacy of these drugs, as well as their propensity to damage the gastrointestinal (GI) epithelium. This toxic action greatly limits the use of NSAIDs in inflammatory bowel disease (IBD) and other chronic pathologies. Fatty acid amide hydrolase (FAAH) degrades the endocannabinoid anandamide, which attenuates inflammation and promotes GI healing. Here, we describe the first class of systemically active agents that simultaneously inhibit FAAH, Cox‐1, and Cox‐2 with high potency and selectivity. The class prototype 4 (ARN2508) is potent at inhibiting FAAH, Cox‐1, and Cox‐2 (median inhibitory concentration: FAAH, 0.031 ± 0.002 μM; Cox‐1, 0.012 ± 0.002 μM; and Cox‐2, 0.43 ± 0.025 μM) but does not significantly interact with a panel of > 100 off targets. After oral administration in mice, ARN2508 engages its intended targets and exerts profound therapeutic effects in models of intestinal inflammation. Unlike NSAIDs, ARN2508 causes no gastric damage and indeed protects the GI from NSAID‐induced damage through a mechanism that requires FAAH inhibition. Multitarget FAAH/Cox blockade may provide a transformative approach to IBD and other pathologies in which FAAH and Cox are overactive.—Sasso, O., Migliore, M., Habrant, D., Armirotti, A., Albani, C., Summa, M., Moreno‐Sanz, G., Scarpelli, R., Piomelli, D. Multitarget fatty acid amide hydrolase/cyclooxygenase blockade suppresses intestinal inflammation and protects against nonsteroidal anti‐inflammatory drug‐dependent gastrointestinal damage. FASEB J. 29, 2616‐2627 (2015). www.fasebj.org